Vulnerabilidad sísmica del laboratorio de investigación de la Universidad Estatal de Bolívar, campus Laguacoto. periodo noviembre 2022-febrero 2023 - Tenelema Chela, Angel Ermel (2023)
This research aims to determine the seismic vulnerability of the Research Laboratory building of the State University of Bolívar; located on the Laguacoto campus, Guaranda Km. 11 2⁄ . via San Simón, through the use of FEMA form P-154 and CYPECAD software. To this end, the visual inspection of the building was carried out, data on its construction was collected and the spectral modal analysis method was applied to simulate the structural behavior of the building in the event of earthquakes. Through the visual inspection using the FEMA form P -154, a score of 1.1 was obtained, which is within the range of qualifications less than 2, which means that the building is at a high level of vulnerability to seismic hazard, because it presents significant damage and deterioration of the structural system since the current local standard was not used in the construction process of the structure. On the other hand, the spectral modal analysis using the CYPECAD program allowed to determine that the building does not meet some of the minimum requirements of seismic resistance established in the Ecuadorian Construction Standard, therefore the behavior and performance of the structure is inadequate. In the first modeling values very close to 1 in Lgz are obtained therefore the first mode of vibration in X the percentage of displaced mass is 96.47% with a degree of freedom in Lgz of 0.57 being translational, in the second mode of vibration in Y is torsional with a percentage of displaced mass of 89.48% and with a value very close to 1 in Lgz of 0.96 the third mode of Vibration is also torsional with 0.99 in Lgz, therefore, it is a structure vulnerable to earthquakes that requires structural improvements to increase its seismic resistance capacity. Therefore, the results obtained indicate that the evaluated building presents high seismic vulnerability, which represents a significant risk to the safety of those who occupy it. The application of structural reinforcement measures is recommended, for this it must be 4 followed up with a specialist in structures and in this way to improve the rigidity of the structure and significantly reduce vulnerability. Keywords: Earthquake, Seismic risk, Vulnerability, Seismic vulnerability, Structural vulnerability, Ecuadorian Building Standards, CYPECAD